Empowering Coastal Communities Through Communal Natural Food Cultivation Training in Sugian Village to Optimize Pearl Oyster Seed Growth: Pemberdayaan Masyarakat Pesisir Melalui Pelatihan Pembudidayaan Pakan Alami Komunal Di Desa Sugian Untuk Optimalisasi Pertumbuhan Benih Kerang Mutiara - Alis Mukhlis; Nunik Cokrowati; Zaenal Abidin; Thoy Batun Citra Rahmadani; Sevia Miranti; Fitrah Putra Amnur (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
Indonesia ranks third globally in Pinctada maxima pearl quality, yet small-scale farmers in Sugian Village, East Lombok face critical challenges with spat survival rates of only 1-5%, far below the economically viable minimum of 25-30%. Limited knowledge and skills in providing quality live feed constitute the primary constraint. This community service program aimed to enhance community capacity in communal live feed cultivation and establish sustainable production systems through technology transfer. The program employed a community-based learning approach with 18 participants, involving socialization, participatory facility development, technical training in Chaetoceros sp. cultivation, and comparative trials between outdoor and laboratory culture systems over four months. The outdoor culture system achieved Chaetoceros sp. density of 3.28 × 10⁶ cells/ml on day-3, only 9.8% lower than laboratory conditions (3.60 × 10⁶ cells/ml). Training significantly improved participants' knowledge from 16.7% (pre-test) to 83.3% (post-test), with 88.9% demonstrating independent culture capability and 46% mastering cell density calculation techniques using haemocytometer. The communal live feed cultivation model proved viable and sustainable, providing knowledge foundation for improving spat survival rates through consistent quality feed provision. This replicable model offers a practical framework for empowering small-scale pearl oyster farmers, potentially increasing spat survival rates from 1-5% toward the target of 25-30% through adoption of proven immersion feeding techniques.